Design all about textiles (Learning Zone Express, 2010)
"The human body is almost constantly in contact with some form of textile, whether it be the clothing we wear or the interiors we live and work in. Join interior designer Brandi Hagen as she showcases samples and explains the different types of natural and synthetic fibres, fabric construction and surface designs."--container.